The Defence of Doctoral Thesis, calling for a Notebook (About the Doctoral Thesis and its Defence of Aurimas Švedas "Soviet Lithuanian Historiography: Official Discourse and its Altematives (1944-1985)" - Gieda, Aurelijus (Lietuvos istorijos studijos, 2006)
-